Phytochemical Studies on the Toxic Compounds of Gladiolus segetum - Abdessemed, D.; Alloui, N.; Dibi, A. (Asian Journal of Chemistry, 2010)
Gladiolus segetum (Iridaceae) is a toxic plant, lethal for livestock. The phytochemistry and biological activity of this plant have not been extensively investigated. The aim of present study is to elucidate the structure of the toxic compounds responsible for the lethal effect of this plant. We report here the isolation from the aerial parts, four anthraquinones: 3,8-dihydroxy-4,7- dimethoxy-1-methylanthraquinone-2-carboxylic acid methyl ester (1), 3,8-dimethoxy-1- methylanthraquinone-2-carboxylic acid methyl ester (2), 1-hydroxy-3,6,7-trimethoxy-8- methylanthraquinone (3), 3,8-dihydroxy-6-methoxy-1-methylanthraquinone-2-carboxylic acid (4) along with quercetin-3-O-β-D-glucopyranoside (5), kaempferol-3-O-β-D-glucopyranoside (6), betulinic acid (7), stigmasterol (8), ergosterol (9), cholesterol (10), ursolic acid (11) and the cytotoxicity effects toward MRC-5 cells of nine fractions obtained from a DCCC. The structures of new natural products anthraquinones 1 and 2 were elucidated by spectral (UV, IR, 1D and 2D NMR and HR-ESI-MS) methods.